2012
DOI: 10.1097/dcr.0b013e3182600db7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on Outcomes of Surgical Resection for Primary Colorectal Cancer

Abstract: From these data, we conclude that surgical resection for colorectal cancer in patients with chronic kidney disease can be performed with acceptable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
1
25
1
Order By: Relevance
“… 16 Meanwhile, a retrospective cohort study of patients with colorectal cancer after surgical resection suggested that those with eGFR <15 mL/min/1.73 m 2 had a poorer overall survival. 15 Similar result was also observed in patients with gastric cancer after gastrectomy. 14 In agreement with previous studies, our data revealed that eGFR < 60 mL/min/1.73 m 2 was associated with higher risk for all-cause mortality among patients with hematologic malignancy and gynecological cancer than that of eGFR > 60 mL/min/1.73 m 2 , whereas no obvious relationship between renal function and death was observed for other cancers.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“… 16 Meanwhile, a retrospective cohort study of patients with colorectal cancer after surgical resection suggested that those with eGFR <15 mL/min/1.73 m 2 had a poorer overall survival. 15 Similar result was also observed in patients with gastric cancer after gastrectomy. 14 In agreement with previous studies, our data revealed that eGFR < 60 mL/min/1.73 m 2 was associated with higher risk for all-cause mortality among patients with hematologic malignancy and gynecological cancer than that of eGFR > 60 mL/min/1.73 m 2 , whereas no obvious relationship between renal function and death was observed for other cancers.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, cancer per se may have a strong influence on mortality rather than a reduced kidney function. 15 , 33 35 Therefore, the mechanisms underlying the impact of renal function on mortality among patients with different primary cancer are complex and remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that renal insufficiency is an independent predictor of postoperative mortality and morbidity for a number of surgical procedures [5][6][7][8][9][10][11][12]. However, among nonsurgical patients, high estimated glomerular filtration rate (eGFR) levels have also been associated with greater mortality, resulting in a U-shaped association of eGFR with mortality [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, their case series was not restricted to cancer operations and had a high proportion of stoma reversals, which present a different perioperative risk profile compared with resectional procedures. Nozawa et al [15]. compared the outcome of elective CRC resection in their institution between CKD and non-CKD groups and found an increased risk of postoperative cardiovascular morbidity in Stage 3-4 CKD, but no effect on overall postoperative mortality.…”
Section: Discussionmentioning
confidence: 98%